Infertilidade e conjugalidade - Rosa, Rita de Cassia Ferrer da (2015)
The aim of this study was to investigate the experience of infertility in conjugality, in order to understand the psyche of couples that search for aid in assisted reproduction techniques. It is an exploratory field research using qualitative and quantitative approaches. It involved a sample of 60 subjects that attended three sessions including three couples each. Data were treated with SPAD.t and SPSS software, which allowed for the frequency calculation and the categorization of verbal material of the participants. The study included a survey of categories of analyzes, which were later analyzed under the theoretical perspective of Analytical Psychology. The results are consistent with previous studies that point to a painful experience brought by infertility, expressed through feelings of sadness, frustration, and failure, that potentially affects the lives of these couples. The results obtained in the protocol of this study also show that in many cases the partners seek and offer support to each other, and often are sensitive to the partner's emotional needs. It was also observed the expression of cooperative actions as a coping strategy of the couple. Resources recruited by the partners to handle this experience reveal the relational quality the couple